Answer:
Lesser number is 6
Explanation:
Let:
1st number = x
2nd number = y
Given that:
Condition 1: one number is two more than three times another:
x = 2 + 3*y
Can be written as:
x-3*y =2 (transferring y term to other side) ........eq (1)
Condition 2: the sum of the numbers is 26.
x + y =26 ............eq (2)
Now subtracting eq (1) from eq (2)
(x + y) - (x-3*y)= 26 -2
Opening brackets: Negative sign will change the signs in bracket
x + y - x + 3*y = 24
Adding like term (x in x and y in y)
4*y = 24
Dividing both sides by 4
y = 6
Putting value of 6 in eq(2)
x + 6 = 26
x = 26 - 6
x = 20
Now x = 20
y = 6
So, Lesser number is 6 (Answer)
I hope it will help you!